Intravenous fentanyl during shoulder arthroscopic surgery in the sitting position after interscalene block increases the incidence of episodes of bradycardia hypotension - Song, Seok Young (The Korean Society of Anesthesiologists, 2011)
BACKGROUND: Episodes of bradycardia hypotension (BH) or vasovagal syncope have a reported incidence of 13-29% during arthroscopic shoulder surgery in the sitting position after an interscalene block (ISB). This study was designed to investigate whether intravenous fentanyl during shoulder arthroscopy in the sitting position after ISB would increase or worsen the incidence of BH episodes. METHODS: In this prospective study, 20 minutes after being in a sitting position, 160 patients who underwent ISB were randomized to receive saline (S, n = 40), 50 µg of fentanyl (F-50, n = 40), 100 µg of fentanyl (F-100, n = 40) or 30 mg of ketorolac (K-30, n = 40) randomly. We assessed the incidence of BH episodes during the operation and the degree of maximal reduction (Rmax) of blood pressure (BP) and heart rate (HR). RESULTS: The incidence of BH episodes was 10%, 15%, 27.5% and 5% in the S, F-50, F-100 and K-30 groups, respectively. Mean Rmax of systolic BP in the F-100 group was significantly decreased as compared to the S group (-20.0 ± 4.5 versus -6.3 ± 1.6%, P = 0.004). Similarly, mean Rmax of diastolic BP in the F-100 group was also significantly decreased (P = 0.008) as compared to the S group. CONCLUSIONS: These results suggest that fentanyl can increase the incidence of BH episodes during shoulder arthroscopic surgery in the sitting position after ISB.